Impact of digitisation on entrepreneurial ecosystems: an Indian perspective. (22nd June 2020) - Tandon, Anushree; Gupta, Ashish; Goel, Puja; Singh, Vinod Kumar
The development of India's start-up base has been the subject of much discussion due to its anticipated ramifications on the entire economy. But this development is coupled with maturity in entrepreneurial ecosystem, which in itself is largely being driven by technology and innovation (Nasscom, 2016). The objective of this paper - is to study the impact of digitisation on the entrepreneurial ecosystem in India, coupled with the rise of digital entrepreneurs especially, in context of start-ups. This paper is divided into different sections that focus on understanding entrepreneurial and digital ecosystems and the emergence of the intersecting field of digital entrepreneurship. The later sections discuss in detail about India's entrepreneurial ecosystem, specifically government support and attempt to draw implications for Indian entrepreneurs who are hoping to build successful technology-based start-ups.